An Integration Of Emotional Intelligence And Leadership Development In The Educational Process To Improve Students' Performance At Medan Aviation Polytechnic: An Innovative Strategy In Human Resource Management - Muhammad Caesar Akbar; Yoses Hasudungan Silaban (Jurnal Multidisiplin Sahombu, 2025)
The increasing use of instant messaging applications, particularly WhatsApp, has had a significant impact on various aspects of life, including the educational environment. This research focuses on analyzing the ethical practices of WhatsApp usage at the Medan Aviation Polytechnic, a higher education institution with unique characteristics and a high demand for communication. This research is motivated by the phenomenon of WhatsApp misuse at the Medan Aviation Polytechnic, such as the spread of misinformation, harassment, and privacy violations. The objective of this research is to analyze the ethical practices of WhatsApp usage at the Medan Aviation Polytechnic, encompassing aspects such as the application's use for academic purposes, communication between students and lecturers, and the social impact of WhatsApp usage. The research method employed is descriptive qualitative with a case study approach. Data was collected through observation, in-depth interviews, and document analysis. The research findings indicate that the ethical practices of WhatsApp usage at the Medan Aviation Polytechnic still need improvement. The research findings show a tendency to use WhatsApp for non-academic purposes, such as gossiping, spreading unverified information, and even harassment. Additionally, this research also found that WhatsApp usage can have positive impacts, such as facilitating communication and collaboration, as well as enhancing access to information. The conclusion of this research highlights the importance of education and socialization regarding the ethical use of WhatsApp at the Medan Aviation Polytechnic. This research recommends the development of ethical guidelines for WhatsApp usage, training for students and lecturers, and regular monitoring and evaluation of ethical practices in WhatsApp usage.